REENGINEERING STRUCTURAL RESILIENCE: A MULTISCALE FRAMEWORK FOR PERFORMANCE-BASED INFRASTRUCTURE DESIGN - Edison Hatoguan Manurung; M. Alit Suryawan; Hotasi Rogate Manurung; Haruto Takahashi (Journal of Moeslim Research Technik, 2026)
Increasing exposure of infrastructure systems to extreme hazards, aging effects, and climate-induced uncertainties has revealed fundamental limitations of conventional strength- and safety-oriented design approaches. Structural performance can no longer be evaluated solely in terms of damage prevention, but must also account for functionality loss, system interdependencies, and recovery capacity. This study aims to reengineer the concept of structural resilience by developing a multiscale framework that integrates resilience explicitly into performance-based infrastructure design. The research adopts an analytical and framework-oriented methodology, combining critical synthesis of performance-based design theories, structural resilience metrics, and systems engineering concepts. Multiscale linkages are established among component-level behavior, system-level functionality, and network-level performance, with explicit consideration of temporal recovery processes. The results demonstrate that resilience is an emergent and time-dependent system property that cannot be inferred directly from component-level performance indicators. Local strengthening strategies are shown to yield limited resilience gains unless supported by system redundancy, connectivity, and recovery-oriented design. The proposed framework reveals hidden vulnerabilities and recovery bottlenecks that remain unaddressed in conventional performance-based approaches. The study concludes that effective resilience-oriented infrastructure design requires a paradigm shift toward multiscale, system-aware, and recovery-informed performance objectives. Embedding these principles into performance-based design provides a robust foundation for enhancing infrastructure reliability, functionality, and societal resilience under extreme and uncertain conditions.